Immunohistochemical evaluation of mast cells and angiogenesis in oral squamous cell carcinoma - Sharma Bhushan; Sriram G; Saraswathi T; Sivapathasundharam B (Wolters Kluwer Medknow Publications, 2010)
Objectives : Angiogenesis is a complex event mediated by angiogenic factors released from cancer cells and immune cells. It has been reported to be associated with progression, aggressiveness and metastases of various malignant tumors including oral squamous cell carcinoma (OSCC). Similarly, mast cells have also been reported to play a role in tumor progression and metastases by promoting angiogenesis. The present study aims at comparison of microvascular density (MVD) and mast cell density (MCD) in normal oral mucosa (NM) and among various grades of OSCC. Materials and Methods : MVD was assessed immunohistochemically using anti-Factor VIII related von Willebrand factor, and MCD using anti-mast cell tryptase in a study sample of 30 cases of OSCC and 10 cases of clinically normal oral mucosa. Results : The mast cells in normal oral mucosa and oral squamous cell carcinoma strongly expressed mast cell tryptase. The density of mast cells and micro vessels were significantly higher in OSCC compared to normal oral mucosa. The MCD and MVD were higher in moderately differentiated OSCC than in well differentiated OSCC ( P > 0.05) and normal oral mucosa ( P < 0.05). Pearson′s correlation revealed a positive correlation between MCD and MVD ( r=0.33; P=0.077). Conclusion : These findings indicate that mast cells may play a role in up regulation of tumor angiogenesis in OSCC probably through mast cell tryptase.